2020
DOI: 10.3389/fpsyt.2020.00445
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Individual Psychotherapy in BDNF Levels of Patients With Mental Disorders: A Systematic Review

Abstract: Background: Brain-derived Neurotrophic Factor (BDNF) is considered the main cerebral neurotrophin and is produced in the central neural system and peripherals. Its levels are reduced in patients with several psychiatric disorders, but it is unclear if the response to psychotherapy can alter its concentration. Objective: To carry out a systematic review evaluating the effects of individual psychotherapy in BDNF levels in patients with mental disorders. Methods: The databases PubMed, EMBASE, PsycArticles, SciELO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Mechanisms that mediate stress-induced behavioral abnormalities are largely unknown. The dysfunctions of the endocrine system, oxidative stress, and neurotrophic factor can be used to explain the pathogenesis of stress-induced psychological disorders ( Claudino et al, 2020 ; McEwen and Akil, 2020 ; Satoh, 2021 ). Myricetin administration (50 mg/kg, i. p., 21 days) has been shown to reduce repeated restraint stress-induced increases in immobility time in mice in the forced swimming and tail suspension test likely through reducing the plasma corticosterone levels and increasing hippocampal GSP-Px activity and BDNF expression in the hippocampus ( Ma et al, 2015 ).…”
Section: The Other Pharmacological Effects Of Myricetin In the Nervous Systemmentioning
confidence: 99%
“…Mechanisms that mediate stress-induced behavioral abnormalities are largely unknown. The dysfunctions of the endocrine system, oxidative stress, and neurotrophic factor can be used to explain the pathogenesis of stress-induced psychological disorders ( Claudino et al, 2020 ; McEwen and Akil, 2020 ; Satoh, 2021 ). Myricetin administration (50 mg/kg, i. p., 21 days) has been shown to reduce repeated restraint stress-induced increases in immobility time in mice in the forced swimming and tail suspension test likely through reducing the plasma corticosterone levels and increasing hippocampal GSP-Px activity and BDNF expression in the hippocampus ( Ma et al, 2015 ).…”
Section: The Other Pharmacological Effects Of Myricetin In the Nervous Systemmentioning
confidence: 99%
“…Our literature review is also incongruent with a recent systematic review of psychotherapy influence on BDNF expression. Claudino et al [ 44 ] stated that there was initial evidence for the role of BDNF as an individual psychotherapy response biomarker [ 44 ]. However, they counted statistically insignificant changes as important.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physical activity is known to positively influence BDNF levels [ 41 ], increasing its expression, probably through epigenetic modification [ 42 , 43 ]. The change of BDNF concentration during individual psychotherapy was recently studied in a review by Claudino et al [ 44 ]; however, the review excluded studies in which group psychotherapy was used, as well as studies in which methylation of BDNF promoter gene was measured. The latter seems important, as disentangling the direct mechanism of action may be essential to clinical practice, for example, providing clues to combining multiple therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate a significant association between neuroplasticity and antidepressant effect mode of action, which implies that the impact of plasticity is conveyed, at least in part, by the BDNF signal [36]. On the other hand, in a recent systematic review assessing the impact of psychotherapy on the levels of BDNF in patients with psychiatric disorders, they found a small amount of research examining the impact of psychotherapies on BDNF and concluded that patients who had only psychotherapy had no rise in BDNF levels; however, those who received concomitant medications had a much greater rise compared to those who had only pharmacological treatment [56]. BDNF was associated with some demographic characteristics of MDD patients like age, sex, family history, and disease duration in the present study.…”
Section: Discussionmentioning
confidence: 99%